Everolimus as second-line therapy for metastatic renal cell carcinoma: a 'real-life' study. (January 2015) - Rizzo, Mimma; Facchini, Gaetano; Savastano, Clementina; Lorenzo, Giuseppe Di; Lucia, Luigi De; Maiorino, Luigi; Casale, Beniamino; Grimaldi, Giuseppe; Formato, Roberta; Febbraro, Antonio; Cartenì, Giacomo
ABSTRACT : Aims: This study, conducted in a 'field-practice' scenario, investigates the effectiveness and safety of everolimus in the second-line treatment of metastatic renal cell carcinoma (mRCC) patients.Patients & methods: mRCC patients, who started everolimus 10 mg/day after failure of first-line VEGF receptor-targeted tyrosine kinase inhibitor, were included in this study. Study end points were treatment response, progression-free survival and tolerability.Results: In total, 100 patients were assessed; the median duration of everolimus treatment was 7.1 months (95% CI: 5.7–8.5). A total of 19% of patients experienced a partial response and 62% of patients reached a stable disease. Median progression-free survival was 8 months (95% CI: 6.7–9.3). A total of 75% of patients experienced adverse events; no grade 4 adverse events were reported.Conclusion: These findings, obtained in a 'field-practice' scenario, support the use of everolimus for mRCC patients who failed one VEGF receptor-targeted tyrosine kinase inhibitor.